Chronic lymphocytic leukemia : molecular genetics, biology, diagnosis, and management - Faguet, Guy B (Humana Press, 2004)
After an interesting in-depth historical perspective, this book reviews recent scientific advances in molecular genetics and biology of chronic lymphocytic leukemia, and discusses clinical aspects of the disease, focusing on diagnosis, prognosis, treatment options, and complications. A final chapter addresses familial and juvenile cases. DNLM: Leukemia, Lymphocytic, Chronic.
Contemporary hematology
Keywords: Leukemia; hematologické nádory; onkologie; Lymphatic Diseases; chronická lymfatická leukemie; Hematologic Neoplasms; Leukemia, Lymphocytic, Chronic, B-Cell; lymfatické nemoci; hematologie a transfuzní lékařství; leukemie